DESAIN MODUL PEMBELAJARAN BERBASIS PEDAGOGI HIJAU UNTUK MAHASISWA CALON GURU BIOLOGI FKIP UNIVERSITAS RIAU - Aftriani, Fadila Aftriani; ', Firdaus LN; ', Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research was conducted to develop the module based Green Pedagogy for students candidates Biology teachers Faculty of Teacher Training and Education University of Riau. The development of module based Green Pedagogy do according Burns model that had five key dimensions, were Content, Context, Process, prespective and Ecological Design (Transformative Learning). The research was conducted in January-June 2015. This research was development (Research & Development) using ADDIE models. The research procedures includes the step of the analysis, design, development and limited testing. Data research were the observation of the campus of University of Riau-Panam, interviews with the Engineering Service Unit (ESU), validation sheet and questionnaire responses of students. Lesson module that have been developed next validated by specialists validator. Based on the results of the validation of the validator shows that the value 3.12 to 3.25 with a valid category for 10 sub-modules that have been developed. Next to see the validity, the validity and usability the lesson module based Green Pedagogy learning, the researcher did limites tested. Respondents in a limited tested were students of Biology Education in 2nd semester academic year 2015 class of 20 people. Conducts sample selection randomly. Sub module tested are sub module 8 and 9 which contains material on air. Based on the results of student responses to the lesson module based Green Pedagogy obtained value ranging from 80.00 to 83.75 for good category and grades from 85.00 to 88.75 for the very good category. The result showed that the lesson module based Green Pedagogy that have been developed are valid and can be implemented on a wider scale. Keywords: Green Pedagogy, Module, Development, Burns Model.